KAJIAN MUTU DAN KEAMANAN PANGAN TRADISIONAL SATE BULAYAK DI TAMAN WISATA SURANADI, KECAMATAN NARMADA, KABUPATEN LOMBOK BARAT - A, Misbah; Suter, I Ketut; Kartika Pratiwi, I Desak Putu (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 4 No 2 (2015): Jurnal ITEPA, 2015)
This study aimed to determine the nutritional and sensory quality, and safety level of microbiological aspects of the traditional food satay bulayak in the Suranadi Tourism Park, West Lombok. This study used a completely randomized design (CRD) in analyzing sensory evaluation and descriptive analysis in analyzing the quality and food security. A total of 6 samples of satay bulayak each was analyzed in terms of its quality and safety with 2 time repetitions. In the sensory test, the data were analyzed by means of analysis of variance and if they had a significant effect then they were followed by Duncan test. The results of this study showed that satay bulayak in Suranadi Tourism Park, Sub-district of Narmada, West Lombok was safe to be consumed bey the highest average values as follows: moisture content of 69.60%, ash content of 0.03%, 6.61% protein content, 15.37% fat, and carbohydrate content of 19.91%. The results of sensory test on bulayak satay with the highest average value of color contained in the Sarillah sample with a value of 5.3 (slightly liked), texture of Sarifah sample of 5.7 (liked), aroma present in the Sarifah sample with a value of 5.2 (slightly liked), there was a sense/taste in Sarillah and Diah samples with values of 5.2 (slightly liked), while the highest overall acceptance was Sarillah samples with values of 5.4 (slightly liked). Total microbial test results obtained the highest score of 2.59 x 10g cfu / g, and negative on Coliform.
Keywords: Quality, food safety, satay bulayak.